(untitled) (Teología, 2019)
The richness and plurality of meanings that the term Sophia has received in speaking of the divine sphere demands careful approach to its use and projection. The author, in this article, intends to take a tour by authors and their insights to be able to have an overview of a complex and rich itinerary.